An Assessment of the Impact of Internship Programs in the Agricultural Technical Schools of Egypt as Perceived by Participants Groups - Catherine W. Shoulders; R. Kirby Barrick; Brian E. Myers (Journal of International Agricultural and Extension Education, 2011)
Experiential learning including student internships has been central to instructional programs in agriculture for decades. If the Agricultural Technical Schools of Egypt are to prepare students for successful careers and to enhance the agricultural economy, teachers must be well-prepared to use this teaching technique. Further, all stakeholders, including students, teachers, parents, headmasters and agribusiness owners, must recognize the importance and impact that implementing a student internship program could have. In this study, all groups identified important contributions to student learning and growth as a result of student participation in the internship program. While several suggestions were posited to improve the program, all agreed that the schools, the communities, the agribusinesses and the students received valuable benefits. The program of student internships in Egypt could be adopted in other countries where the agricultural economy could be improved through a better prepared agricultural workforce.
Keywords: Internships; Egypt; Experiential learning; Impact assessment